2016
DOI: 10.1210/jc.2015-3766
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Delay in Diagnosis in Outcomes in MEN1: Results From the Dutch MEN1 Study Group

Abstract: There is a clinically relevant delay in MEN1 diagnosis in families because of a lag time between the diagnosis of an index case and the rest of the family. More emphasis should be placed on the conduct of proper counseling and genetic testing in all eligible family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 22 publications
2
37
2
Order By: Relevance
“…Data from the Italian database confirm that, thanks to the genetic test, the average age of MEN1 diagnosis is about 10 years younger in family members as compared with that of the proband itself. This is at variance with data obtained in other European countries, where a delay in diagnosis in family members has been reported [29]. Moreover, the mean average age of the first clinical manifestation in probands occurred about 10 years before the diagnosis of MEN1, whereas in familial members the average age of MEN1 diagnosis occurred about 1 year before the first clinical manifestation of the syndrome.…”
Section: Discussioncontrasting
confidence: 89%
“…Data from the Italian database confirm that, thanks to the genetic test, the average age of MEN1 diagnosis is about 10 years younger in family members as compared with that of the proband itself. This is at variance with data obtained in other European countries, where a delay in diagnosis in family members has been reported [29]. Moreover, the mean average age of the first clinical manifestation in probands occurred about 10 years before the diagnosis of MEN1, whereas in familial members the average age of MEN1 diagnosis occurred about 1 year before the first clinical manifestation of the syndrome.…”
Section: Discussioncontrasting
confidence: 89%
“…We found that the mean age at MEN1 diagnosis was only slightly higher for index cases than for family members. Our results, compared with other papers, suggest that we usually establish a MEN1 diagnosis earlier, and there is a smaller difference between the age at diagnosis in index cases and family members [13,14,23,24]. That is possible because of early implementation of genetic analysis for all the first-line family members on the basis of clinical presentation.…”
Section: Discussionsupporting
confidence: 51%
“…Delays in diagnosis and/or the onset of tumor surveillance among MEN1 -carriers are associated with increases in both morbidity and mortality (39). For first-degree relatives of MEN1 carriers with unknown mutational status, we advocate annual serum prolactin from age five and annual serum calcium (corrected for albumin) from age 10 years.…”
Section: Multiple Endocrine Neoplasia Type 1 (Men1)mentioning
confidence: 99%